PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ANDROID PADA MATA PELAJARAN DASAR-DASAR DESAIN KOMUNIKASI VISUAL KELAS X DKV DI SMK NEGERI 1 PASAMAN - Silwi Uswatun Hasanah; Irsyadunas; Rini Novita (JURNAL ILMIAH SAINS TEKNOLOGI DAN INFORMASI, 2024)
The aim of this research is to develop valid and practical learning media for the basics of visual communication design. The process of learning the basics of visual communication design at SMKN 1 Pasaman is not optimal, this is caused by several problems, namely the availability of learning media only in the form of printed books that students borrow from the school library. This causes students to not understand the learning material and be less motivated to study and cause low student grades. Based on the data obtained, the students' KKM completion score was only 53%. This research uses the Research and Development (R&D) research and development method with the ADDIE model which consists of 5 stages, namely Analysis, Design, Development, Implementation and Evaluation at each stage. This research involved 36 class X DKV students who took part in learning the basics of visual communication design. The results of this research are Android-based learning software that can be used as a complement to the learning process, especially in the basics of visual communication design subjects. Data collection techniques are in the form of observations and questionnaires, while data collection instruments are in the form of validity questionnaires and practicality questionnaires. The data analysis technique uses a Likert scale with the Aiken formula. The results of this research show that the validity value of the media is an average of 81.53% in the "Very Valid" category, while the validity of the material is an average of 93.85% in the "Very Practical" category and the teacher's practicality assessment is an average of 81.77% in the "Practical" category. " while students' practicality assessment averaged 83.3% in the "Practical" category.